2012
DOI: 10.1136/heartjnl-2011-301269
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic impact of copeptin and high-sensitivity cardiac troponin T in patients with pre-existing coronary artery disease and suspected acute myocardial infarction

Abstract: ClinicalTrials Gov number NCT00470587.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 42 publications
11
44
0
2
Order By: Relevance
“…17 We have previously reported that the combination of high sensitivity troponin T (hsTnT) and copeptin, a biomarker of endogenous stress, is helpful in the diagnostic process to rule out ACS. [10][11][12][13][14] Copeptin is the c-terminal of the vasopressin precursor hormone and is co-secreted with the hormone by the neurohypophysis as a response to endogenous stress. 14 One prospective study using the copeptintroponin algorithm has been presented with the results indicating this regimen to be a safe approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 We have previously reported that the combination of high sensitivity troponin T (hsTnT) and copeptin, a biomarker of endogenous stress, is helpful in the diagnostic process to rule out ACS. [10][11][12][13][14] Copeptin is the c-terminal of the vasopressin precursor hormone and is co-secreted with the hormone by the neurohypophysis as a response to endogenous stress. 14 One prospective study using the copeptintroponin algorithm has been presented with the results indicating this regimen to be a safe approach.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Examples of the proposed strategies are the use of hsTn in combination with a risk score, 4 the use of a second hsTn test analysed after 1 hour, 5 the use of undetectable hsTn levels [6][7][8][9] and the use of a combination of hsTn and another biomarker. [10][11][12][13][14][15][16] In older patients higher hsTn cut-off levels have been suggested to improve diagnostic performance. 17 We have previously reported that the combination of high sensitivity troponin T (hsTnT) and copeptin, a biomarker of endogenous stress, is helpful in the diagnostic process to rule out ACS.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal release pattern of copeptin in our study was characterized by increased values very early after symptom onset, a peak in ambulance or at admission, and a rapid decrease within the first hours after admission. Copeptin concentrations returned to baseline in all diagnoses after 12-36 h. Several studies have shown that copeptin values are increased in patients with AMI at admission, especially in early presenters (4,6,10,11,(17)(18)(19)(20)(21)(22)(23). We were able to illustrate for the first time that copeptin values were al- Thirty-five patients with AMI and SOT ≤180 min and 20 patients with AMI and SOT >180 min were included in this study.…”
Section: Discussionmentioning
confidence: 63%
“…No study has yet been designed to analyze whether addition of copeptin to hs-cTn is superior to simply decreasing the cut-off of the hs-cTn assay. At least, post hoc analysis of the published ROC curves does not support superiority [23].…”
Section: This Issue Of Clinical Chemistry and Laboratory Medicinementioning
confidence: 99%